"Do you hear what these are saying?" (Mt 21:16): Children and their role within Matthew"s narrative - Weaver, Dorothy J. (HTS teologiese studies, 2019)
This article sketches the broad outlines of Matthew’s ironic portrayal of children, examining first the ‘lower level’ of the narrative (i.e. the way things appear to be in the everyday world) and then the ‘upper level’ of the narrative (i.e. the way things truly are from the ‘God’s-eye’ perspective). When viewed from the ‘lower level’ of Matthew’s narrative, the everyday circumstances of children reflect the nurture of their parents as well as significant challenges: debilitating physical conditions, serious illnesses, military violence and premature childhood death. In addition, children occupy the lowest rung on the 1st-century Mediterranean social ladder, a status they share with slaves. But on the ‘upper level’ of his narrative, from the ‘God’s-eye’ perspective, Matthew turns everyday reality for children on its head in ironic fashion. Emmanuel, the ‘God who is with us’, appears as a ‘child’ who has just ‘been born’ and who exhibits all the powerlessness and vulnerability of such a ‘child’. In a violent showdown between ‘King Herod’ and the one ‘who has been born king of the Jews’, it is Herod, the powerful ruler, who dies, while the vulnerable ‘child’ ends up safely in Nazareth. Throughout his ministry, Jesus heals children along with adults. To the apparent chagrin of his disciples, Jesus lays hands on children in an act of blessing. He commends the messianic praises of children, in contrast to the outrage of the Jewish leadership. Moreover, Jesus proclaims that it is ‘to such as these [children] that the kingdom of heaven belongs’.